21. Longitudinal fMRI assessment in chronic spinal cord injury treated by intrathecal baclofen – Pilot data. Issue 3 (March 2015) - Keller, Jiri; Jech, Robert; Stetkarova, Ivana
<x xml:space="preserve">Abstract</x> Introduction Spasticity is a frequent disabling sign of upper motor neuron lesion in chronic spinal cord injury (SCI). In severe cases intrathecal baclofen (ITB) is recommended as a choice of effective treatment. Baclofen, being as a strong GABAB agonist, modulates cortical and spinal inhibitory circuits. The aim of this study was to assess longitudinal changes in brain activation after continuous ITB delivery during simple motor tasks performed by functional magnetic resonance imaging (fMRI). Material and Methods Two subjects (27 and 35 years-old males, 5.5 years after SCI) with chronic posttraumatic cervical spinal cord injury at C4–5 level underwent ITB pump implantation (Synchromed II, 20 ml, Medtronic). Spasticity was assessed by Modified Ashworth Scale (MAS, 0–4). Both subjects were studied by 1.5T fMRI with three tasks employed: (i) finger-tapping and mental movement simulating, (ii) finger taping and (iii) foot flexion. Tasks were performed before, 12 weeks and one year after ITB pump implantation. Analysis was processed in SPM8 using the FWE corrected threshold (p < 0.05). Results Both patients were classified as AIS-A and they presented no active movements of lower limbs. In both subjects, MAS score declined in the lower extremities from 4 to 1 before and after ITB implantation, respectively. Before-ITB pump implantation fMRI showed weak activations in all tasks. Post-ITB tasks extensively raised activation in the motor system network, namely the primary sensorimotor cortex and supplementary motor area. In one year follow-up, the activation in foot-flexion mental tasks were detectable only in one of the subjects, with slightly increased volume. One of the most important factors, influencing all the results, is subject motion. Conclusions Continuous ITB administration relieving spasticity in SCI patients was associated with increased activation of sensorimotor cortex. ITB treatment may cause distant functional reorganization of sensorimotor network probably by increased GABAB-mediated inhibitory activity at cortical level. Supported by Research Projects PRVOUK P34, UNCE 204010/2012 and IGA NT12282.